Activity-Dependent and Experience-Driven Myelination Provide New Directions for the Management of Multiple Sclerosis. Issue 6 (June 2016) - Jensen, Samuel K.; Yong, V. Wee
Abstract : Despite an appreciation of the importance of myelination and the consequences of pathological demyelination, the fundamental mechanisms regulating myelination are only now being resolved. Neuronal activity has long been considered a plausible regulatory signal for myelination. However, controversy surrounding its dispensability in certain contexts and the difficulty in determining to what degree it influences myelination has limited its widespread acceptance. Recent studies have shed new light on the role of neuronal activity in regulating oligodendrogenesis and myelination. Further, the dynamics of myelin in adulthood and the association between skilled learning and myelination have become increasingly well characterized. These advances present new considerations for the management of multiple sclerosis and open up new approaches to facilitate remyelination following pathological demyelination. Trends: Myelin has been demonstrated to be a highly dynamic structure with a large degree of heterogeneity between different CNS regions. Renewed evidence demonstrates that oligodendrocytes respond strongly to neuronal activity where increased activity promotes oligodendrogenesis, increases myelin thickness, biases axon selection towards active axons, and enhances myelinating potential. White matter fractional anisotropy is positively correlated with skilled learning and adaptive myelination is required for motor skill learning. These changes are likely driven by alterations in neuronal activity patterns during learning. Sensory and environmental input are required for the proper myelination of both sensory regions responsible for signal processing as well as associated higher order regions within the CNS.